2022
DOI: 10.1007/s40095-022-00502-8
|View full text |Cite
|
Sign up to set email alerts
|

Energy and exergy analysis of solar dryer with triple air passage direction collector powered by a wind generator

Abstract: The objective of this study is to thermodynamically investigate the performance of solar dryers by delaying the airflow in the collector. For this reason, a triple air path on a single pass collector with the fan powered by a wind generator was developed and evaluated in a very humid climate. The evaluation parameters were drying efficiency, energy and exergy analysis, sustainability assessment, CO2 mitigation ability and effective moisture diffusivity of dried product. The results showed that the collector ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Thus the overall external uncertainties from the measurements are given by Philip et al (2022) as follows 1Where UT, Urh, Usol and, Um are the uncertainty in the measurement of Temperature, relative humidity, solar radiation and, the mass of the product with their reading errors. For each measurement, the uncertainty (Ux) is given as (Ndukwu et al, 2022b) 2 w1, w2 and wn are the experimental uncertainty in the variables z1, z2 and zn.…”
Section: Experimental Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the overall external uncertainties from the measurements are given by Philip et al (2022) as follows 1Where UT, Urh, Usol and, Um are the uncertainty in the measurement of Temperature, relative humidity, solar radiation and, the mass of the product with their reading errors. For each measurement, the uncertainty (Ux) is given as (Ndukwu et al, 2022b) 2 w1, w2 and wn are the experimental uncertainty in the variables z1, z2 and zn.…”
Section: Experimental Uncertaintiesmentioning
confidence: 99%
“…Triple-pass solar air heater with thermal storage has been investigated by Keavan and Arjunan (2018) for drying mints while Yassien et al (2020) integrated nets of tubes below the absorber in their design. Ndukwu et al (2022b) studied the drying kinetics of cocoyam slices with a partitioned single-pass indirect solar dryer. They concluded that the two-term model best predicted the drying kinetics of the sliced cocoyam in the dryer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, drying has been shown to use 6 to 30 times more energy than cooling and freezing (Machala et al, 2022). As a result, reliance on fossil fuels to meet heat demand during drying will emit considerable amounts of carbon into the atmosphere (Ndukwu et al, 2023). Thus, it is vital to switch from fossil-fueled dryers to clean energy sources (Chowdhury et al, 2020).…”
Section: Introductionmentioning
confidence: 99%